Biomarkers Of Oxidative Stress In Chronic Diseases: Clinical And Laboratory Perspectives (The Review of Diabetic Studies, 2024)
Oxidative stress is a common cause of many long-term health problems, such as diabetes, cancer, heart disease, neurological disease, chronic kidney disease, and kidney disease. An excess of reactive oxygen species (ROS) can harm lipids, proteins, and nucleic acids by going beyond the body's antioxidant defenses. Measuring oxidative stress has become more important for screening, diagnosing, and evaluating treatment in the last few years. Malondialdehyde, total antioxidant capacity, 8-hydroxy-2′-deoxyguanosine, advanced oxidation protein products, and protein carbonyls are some common biomarkers. In order to test these biomarkers in a lab, it is important to carefully control all the factors that come into play before, during, and after the analysis. The integration of oxidative stress biomarkers, examined in this review alongside the challenges in their assessment, facilitates optimal disease risk classification and patient treatment.